2013
DOI: 10.1016/s0187-6236(13)71065-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of model-based PM2.5 emission factors for on-road mobile sources in Mexico

Abstract: RESUMENSe investigan los resultados del empleo del modelo US-EPA MOVES2010a para calcular los factores de emisión del parque vehicular mexicano, y se comparan dichos resultados con las estimaciones del Inventario Nacional de Emisiones de México (INEM) de 2005. El estudio muestra que los factores de emisión PM2.5 basados en modelos, actualizados a partir de estudios recientes, pueden tener un impacto significativo en la estimación de emisiones de PM2.5 procedentes de fuentes móviles en México. Porcentajes mayor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Large numbers of vehicles on the road emit more particles than fewer vehicles. 42 However, variation of traffic volume was not strongly related to PM 2.5 variation, and was not a significant factor for the variations of increasing PM. 43 Also, older vehicles tend to emit more PM 2.5 to ambient air.…”
Section: Air Soil and Water Researchmentioning
confidence: 79%
See 2 more Smart Citations
“…Large numbers of vehicles on the road emit more particles than fewer vehicles. 42 However, variation of traffic volume was not strongly related to PM 2.5 variation, and was not a significant factor for the variations of increasing PM. 43 Also, older vehicles tend to emit more PM 2.5 to ambient air.…”
Section: Air Soil and Water Researchmentioning
confidence: 79%
“…43 Also, older vehicles tend to emit more PM 2.5 to ambient air. 42 Both emissions of gasoline- and diesel-fueled vehicles can contribute to PM 2.5. For example, gasoline-fueled vehicles contribute 17.2% and diesel vehicles contribute 8.1% to PM 2.5 in Seoul, Korea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies indicate that the use of the model can improve the emissions estimates of inventories in Mexico with respect to older emission models (Zavala et al, 2013;Guevara et al, 2017). However, its efficient application to other countries requires the adjustment of multiple internal parameters, among which the emission factor databases are of key importance.…”
Section: Comparison With Moves2014 Mexico Modelmentioning
confidence: 99%
“…First, the contribution of single human activity to PM 2.5 varies greatly. For instance, some have studied the relationship between vehicle emissions and PM 2.5 [30,31]. In addition, Guo et al [32] found that the expansion of logistic services had the greatest impact on air pollution, but Gross Domestic Product (GDP) and urban population growth were only weakly correlated with air pollution.…”
Section: Introductionmentioning
confidence: 99%